The Human Blood Platelets as a Molecular Mosaic Its Role in Aggregation and Thrombus Formation - Mehrishi, J. N (Thrombosis and Haemostasis, 1971)
On the surface of human blood platelets various types of groups are present - sulphydryl groups, positively charged amino groups and at least three types of anionogenic groups. The numbers of these groups on a per cell basis have been calculated and then* relative contributions to the net charge determined. Two arrangements for the distribution of the groups in the cell periphery have been proposed. Such studies provide a molecular basis for many reactions taking place at the cell surface. The role of these groups in platelet aggregation and thrombus formation is discussed